Foye's principles of medicinal chemistry - Roche, Victoria F.; Zito, S. William; Lemke, Thomas L.; Williams, David A. (Philadelphia, PA : Wolters Kluwer/Lippincott Williams & Wilkins, 2019)
"With expert contributions from experienced educators, research scientists and clinicians, Foye's Principles of Medicinal Chemistry, Eighth Edition is an invaluable resource for professional students, graduate students and pharmacy faculty alike . This 'gold standard' text explains the chemical basis of drug action, emphasizing the structure-activity relationships, physicochemical-pharmacokinetic properties, and metabolic profiles of the most commonly used drugs"--
Previous ed.: 2013.
Keywords: Farmakologi; Farmaceutisk kemi; Pharmaceutical chemistry; Pharmacology; Pharmaceutical chemistry -- Physiological effect; Pharmaceutical chemistry; Pharmacology; Pharmacology; Pharmaceutical chemistry